PWE-324 A feasibility study investigating the association between self-efficacy and the success of patients on the eras programme. (22nd June 2015) - Edis, H; Maxwell-Armstrong, C; Ferguson, E
Abstract : Introduction: Perceived self-efficacy may be associated with patient outcomes on the Enhanced Recovery after Surgery (ERAS) programme. This feasibility study investigates the association between level of perceived self-efficacy and length of stay in hospital (LOSH) (a measure of success on the ERAS programme). The ERAS programme is a multi-model approach to surgical care which optimises patient physical condition by minimising the stress imposed on the body pre-, intra- and post-operatively. Primary outcome measure: Is there statistical significance in the relationship between self-efficacy score and LOSH after colorectal surgery on an ERAS programme? Secondary outcome measure: Is there statistical significance in the relationship between the component parts of self-efficacy measured (recovery locus of control, health anxiety and value and optimism) and LOSH? Method: Single-centre, quantitative. Study questionnaire was an amalgamation of 5 validated questionnaires: General Self-efficacy scale, Recovery Locus of Control, Whiteley Index, Health Value and Life Orientation Test. Non-random convenience sampling was used to recruit continuously over 6 months (March-Sept 2014). Questionnaire completed twice by each participant: pre-operatively and post-operatively giving an overall self-efficacy score which was correlated against LOSH. Results were analysed using Pearson–s Correlation. Results: Study sample N=30. There was a slight positive correlation between the primary variables but this carried no statistical significance (p = 0.832). No statistical significance found in the associations between LOSH and the secondary variables. The most notable correlation was found between the Family and Friend Test for patient satisfaction and LOSH. Conclusion: Previous research has found self-efficacy positively impacts recovery in a variety long-term health conditions. It is possible that with a greater sample size a similar relationship could be demonstrated with ERAS patients. Finding ways to optimise psychological state prior to major surgery in terms of an individual–s self-efficacy, could have dramatic effects in reducing LOSH and improving overall patient satisfaction. The present study has led the way into exploring a new research relationship. This feasibility study should be the foundation for a larger scale, randomised study. Disclosure of interest: None Declared.